Spinal Cord Stimulation (SCS)—The Implantable Systems Performance Registry (ISPR) - Schultz, David M. (Neuromodulation, 2016)
OBJECTIVES: The Implantable Systems Performance Registry (ISPR) was created to monitor the product performance of Medtronic Spinal Cord Stimulation (SCS) and implanted intrathecal drug infusion systems available in the United States. MATERIALS AND METHODS: Data were collected on 2605 patients from 44 centers from various geographic regions across the United States implanting and following patients with SCS systems between June 25, 2004 and January 31, 2014. Actuarial life table methods are used to estimate device performance over time. Of the 2605 patients, 1490 (57.2%) were female, 1098 (42.1%) were male and 17 (0.7%) did not provide gender data. The average age at enrollment was 56.3 years (range: 4–97, SD = 14.3) and average follow‐up time was 20.1 months (SD = 22.5). RESULTS: Currently the estimates of device survival from neurostimulator‐related events exceed 97% for all neurostimulator models across the applicable follow‐up time points and all applicable extension models had greater than 95% survival from extension events. The majority of product performance events were lead‐related. At 5 years of follow‐up, all applicable lead families, with the exception of the Pisces‐Quad LZ family, had greater than 75% survival from lead events. CONCLUSIONS: The ISPR is designed to serve as an ongoing source of system and device‐related information with a focus on “real‐world” safety and product performance. ISPR data continue to be used to guide future product development efforts aimed at improving product reliability and quality.